EVALUATION OF ANTICONVULSANT ACTIVITY OF PREMNA HERBACEA (ROXB.) ROOT EXTRACTS IN ISONIAZID AND STRYCHNINE-INDUCED CONVULSIONS - Ad, Chimbalkar; Ns, Vyawahare (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present investigation was to evaluate the anticonvulsant potential of three different extracts of roots of Premna herbacea (Roxb.) in mice. The preclinical screening models such as isoniazid (INH)- and strychnine (STR)-induced convulsion were selected for the study. Methods: The three different extracts of P. herbacea, i.e., ethanolic (PHE), petroleum ether (PHP), and chloroform (PHC) were prepared as per standard procedures and evaluated at three different doses (100, 200, and 400 mg/kg) and screened with above-mentioned INH and STR-induced convulsions. Results: In INH model, PHC 200 mg/kg and 400 mg/kg showed dose-dependent delay in onset of convulsion (p<0.05 and p<0.01) along with protection of 33.33% of mice. The PHP 400 mg/kg also showed a significant delay in the onset of convulsion (p<0.05) along with protection of 16.66% of mice. In STR-induced model, none of the extracts was effective to delay the onset of convulsion; however, PHC 400 mg/kg protected 16.66% of mice. Conclusion: The results confirmed dose-dependent anticonvulsant activity of P. herbacea PHC in INH-induced convulsions.